Fines versus damages: Experimental evidence on care investments - Florian Baumann; Tim Friehe; Pascal Langenbach (Max Planck Institute for Research on Collective Goods, 2020)
This paper studies the differential effects of fines and damages on people's investment in accident prevention. We report results from a laboratory experiment in which monetary payoffs are maintained across the two policy instruments. While standard theory predicts no difference in behavior, we find that potential injurers invest substantially more money in accident prevention when they are subject to damages instead of a fine. We discuss possible behavioral channels that may explain our findings.
hdl:21.11116/0000-0006-5E7C-7
Keywords: H62; K42; 330; Externality; Care; Liability; Damages; Fine